Major Depressive Disorder and Sleep Medicine - Guay, Angel, author 647969; Fallon, Miya author 647970 (Delhi, India : College Publishing House, 2012)
Major depressive disorder (MDD) (also known as recurrent depressive disorder, clinical depression, major depression, unipolar depression, or unipolar disorder) is a mental disorder characterized by an all-encompassing low mood accompanied by low self-esteem, and by loss of interest or pleasure in normally enjoyable activities. This cluster of symptoms (syndrome) was named, described and classified as one of the mood disorders in the 1980 edition of the American Psychiatric Association's diagnostic manual. The term "depression" is ambiguous. It is often used to denote this syndrome but may refer to any or all of the mood disorders. Major depressive disorder is a disabling condition which adversely affects a person's family, work or school life, sleeping and eating habits, and general health. In the United States, around 3.4% of people with major depression commit suicide, and up to 60% of people who commit suicide had depression or another mood disorder.